Oral inflammatory load predicts vascular function in a young adult population: a pilot study - Hong, Ker-Yung; Ghafari, Avin; Mei, Yixue; Williams, Jennifer S.; Attia, Dina; Forsyth, Jourdyn; Wang, Kevin; Wyeld, Trevor; Sun, Chunxiang; Glogauer, Michael; King, Trevor J. (Frontiers in Oral Health, 2023)
The periodontium is a highly vascularized area of the mouth, and periodontitis initiates negative functional and structural changes in the vasculature. However, mild oral inflammation, including levels experienced by many apparently healthy individuals, has an unclear impact on cardiovascular function. The purpose of this pilot study is to investigate the effects of objectively measured whole mouth oral inflammatory load (OIL) on vascular function in apparently healthy individuals. Methods: In this cross-sectional and correlational analysis, we recruited 28 young (18-30 years) and systemically healthy participants (16 male, 12 female). Using oral neutrophil counts, a validated measure for OIL, we collected participant's mouth rinse samples and quantified OIL. Blood pressure, arterial stiffness (pulse-wave velocity) and endothelial function (brachial artery flow-mediated dilation) were also measured. Results: Only oral neutrophil count significantly predicted flow-mediated dilation % (p= 0.04; R 2 = 0.16, β = -1.05) and those with OIL levels associated with >2.5 x 10 5 neutrophil counts (n= 8) had a lower flowmediated dilation % (6.0 ± 2.3%) than those with counts associated with gingival health with less than 2.5 x 10 5 neutrophil counts (10.0 ± 5.2 %, p= 0.05). There were no significant predictors for arterial stiffness. Conclusion: We found that OIL was a predictor of reduced flow-mediated dilation. An impairment in flow-mediated dilation is an indicator of future possible risk of cardiovascular disease -one of the leading causes of death in North America. Therefore, this study provides evidence for the importance of oral health and that OIL may impact endothelial function.